Analisis Motivasi dan Persepsi Mahasiswa PPG Calon Guru Melalui Pengembangan Media Ajar Interaktif - Wresni, Dhina Shinto; Prihastari, Ema Butsi; Sari, Ayu Istiana; Enggarwati, Ressa; Anggraeni, Novitasari Dyah; Andrian, Yohanes Oscar (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2025)
This study aims to analyze the motivation and perceptions of pre-service teacher education students in the English Language Education Program at Universitas Slamet Riyadi regarding the implementation of the Leadership Project in the form of developing interactive teaching media for English language learning. The study employed a qualitative descriptive approach with 32 participants from the 2024/2025 academic year. Data were collected through an online questionnaire using Google Forms, consisting of Likert scale items and open-ended questions, as well as weekly student reflections during the implementation at partner schools. The data were analyzed using thematic analysis, which involved data reduction, theme categorization, meaning interpretation, and descriptive narrative presentation. The findings revealed that 80% of respondents had high initial motivation, maintained positive perceptions before and after implementation, and rated the developed media as “useful” or “very useful” for learning. The types of media produced included educational board games, digital quizzes, e-magazines, ReadVenture, and AR Books, all of which effectively enhanced students’ cognitive and psychomotor engagement. The study recommends expanding the research subjects to other study programs, employing experimental designs to measure learning outcomes, and incorporating cost-benefit analysis to ensure the sustainability of interactive teaching media.